A People's History of the Second World War : Resistance Versus Empire - Gluckstein, Donny 1954- (Pluto Press, 2012)
A People's History of the Second World War unearths the fascinating history of the war as fought 'from below'. Until now, the vast majority of historical accounts have focussed on the conflict between the Allied and Axis powers for imperialist mastery. Donny Gluckstein shows that in fact between 1939 and 1945 two distinct wars were fought – one ‘from above’ and one ‘from below’. Using examples from countries under the Nazi heel, in the colonies and within the Axis and Allied camps, Gluckstein brings to life the very different struggle of the people's and resistance movements which proliferated during the war. He shows how they fought not just fascism, but colonialism and empire, and were betrayed by the Allies at the war’s end. This book will fundamentally challenge our understanding of the Second World War – both about the people who fought it and the reasons for which it was fought